(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
The study aims to explore the strategic development directions of commercial banks through the digitalization and automation of accounting information. The research applies comparative analysis, review of international practices, and examination of national financial reporting to identify current challenges and opportunities. The findings reveal that digital transformation of accounting processes improves accuracy, transparency, and efficiency in financial management, while also enhancing risk control and decision-making quality. The study concludes that integrating advanced digital tools and automated systems into accounting practices is a key driver for the sustainable strategic growth of commercial banks.